SOME ASPECTS OF THINKING AND CORRECT WRITING CULTURE IN MODERN METHODOLOGY - Kajaia, Manana (European Scientific Journal, ESJ, 2014)
Language diversity shows how different is the way of thinking and world vision in different nations. It determines our social and cultural consciousness. Therefore, it is very important to develop correct speaking and writing culture in students.